Climatic and Landscape Conditions in the Middle Volga Region at the Turn of Miocene and Pliocene - L.I. Linkina; E.V. Petrova (Учёные записки Казанского университета: Серия Естественные науки)
This paper presents the results of paleogeographic reconstructions of the climate and landscape conditions in the Middle Volga region at the turn of Miocene and Pliocene. This period is of special interest due to the rearrangement of the entire landscape environment, for which it became similar to the modern one. The climatic and landscape conditions were reconstructed using the lithological, palynological, and geomorphological data.